Customer trading and information in foreign exchange markets - Geir Høidal Bjønnes; Dagfinn Rime (University of Oslo, Department of Economics, 2000)
Recent research point to the possible existence of private information in foreign exchange markets. Dealers claim that customer orders are their most important source of private information, and that banks with a large customer base have a competitive advantage. In this paper we test hypotheses on effects of private information using observations on customer trades, and the identity of the counterparties the dealers trade with. We find that customer trades influence the trading decision. Neither customer trades nor counterparty identity affect pricing decisions. Dealers do not price discriminate between dealers, but they do price discriminate customers. Spreads to customers are wider than to other dealers.
Keywords: F31; G15; 330; Foreign Exchange; Microstructure; Customer trading; Private information; Devisenmarkt; Devisenhandel; Mikrostrukturanalyse; Norwegen